PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI DENGAN PENERAPAN GOOD GOVERNANCE SEBAGAI VARIABEL MODERASI - Anggiriawan, Budi; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2015)
LPD (Village Credit Institutions) has proved to be capable of contributing to the development and prosperity of the local villagers. Along with these developments, it is possible there is a problematic LPD because of mismanagement. The existence of a troubled LPD can not be separated from organizational culture and leadership style on each LPD, therefore the advancement of LPD highly depends on the administrators and managers, especially the leader. The inconsistency of the results of research on the influence of leadership style and organizational culture on performance indicates the effect of other variables as moderating variables. The results showed that the implementation of good governance moderates the influence of leadership style and organizational culture on organizational performance. It is supported by each of the variables of leadershipstyle, organizational culture, and good governance affect the performance of the organization. Keywords : Leadership style , organizational culture, implementation of good governance, organizational performance, and LPD